A logistical development strategy for Mozambique: needs and oportunities - Martins, A.; Menezes, J.; Crespo de Carvalho, J. (Building bridges for African Business & Development, 2004)
Although Mozambique is a former Portugeuse colony, cultural, historical and emotional bonds remain. he civil was that followed independence devastated country's infrastructures but efforts are being made to recover the economy and expand entrepreneurial expectations. The purpose of this paper is to find ways to develop Mozambique frmo a logistical perspective. Micro and macro analysis will be used in order to identify development catalysts. Logistical concepts will be used in the analysis. the results of this paper are the selection of a macro scenario of logistical develpment and its overall economical and social potential consequences.